Kajian Perbandingan Pengungkapan Corporate Social Responsibility: Analisis Deskriptif pada Sektor Perusahaan Pertanian Perkebunan - Nashirotun Nisa Nurharjanti; Erma Setiawati; Eni Kusumawati; Fatchan Achyani (Universitas Katolik Soegijapranata Semarang, 2021)
Disclosure of Corporate Social Responsibility (CSR) reflects a company’s concern for its surrounding environment. This study examines the level of CSR disclosure among companies in the plantation agriculture sector. The aim is to determine the level of CSR compliance presented in the Sustainability Report based on GRI standards. The results of this study indicate that PT. Astra Agro Lestari Tbk, PT Bukit Asam Tbk, PT. Eagle High Plantations Tbk, PT. London Sumatra Indonesia Tbk, PT. Sinar Mas Agro Resources Technology Tbk and PT. Sawit Sumbermas has been continuously disclosing CSR with GRI Standards even though there are a number of indicators in GRI Standards that have not been disclosed. However, the application of CSR disclosure has been done both internally and externally. Especially PT. Astra Agro Lestari Tbk, which has an average percentage of 2016-2018, has a record of 75% which is included in the Applied Good category. Where the general disclosure compliance rate was 87.50%, compliance in management approach 100%, compliance in environment 96.67%, and compliance in social 90.2%